2013
DOI: 10.1021/jf400914e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hepatoprotective Peptide in Wheat Gluten Hydrolysate against d-Galactosamine-Induced Acute Hepatitis in Rats

Abstract: A hepatoprotective peptide, pyroglutamyl leucine (pyroGlu-Leu), was identified in wheat gluten hydrolysate through an in vivo activity-guided fractionation approach based on D-galactosamine-induced acute hepatitis in rats and fractionation of peptides with large-scale preparative ampholine-free isoelectric focusing. The active acidic fraction predominantly consisted of pyroglutamyl peptides and free pyroglutamic acid. Pyroglutamyl peptides were derivatized with phenyl isothiocyanate after removal of a pyroglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 19 publications
3
57
1
Order By: Relevance
“…Our research group recently reported that pyroGlu-Leu suppressed D-galactosamine (D-GalN)-induced hepatitis in rats (Sato et al, 2013). We have also found that pyroGlu-Leu decreases plasma TNF-α and IL-6 levels in LPS-administered mice (unpublished data).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our research group recently reported that pyroGlu-Leu suppressed D-galactosamine (D-GalN)-induced hepatitis in rats (Sato et al, 2013). We have also found that pyroGlu-Leu decreases plasma TNF-α and IL-6 levels in LPS-administered mice (unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…Higaki-Sato et al (2006) reported that significant amounts of free pyroglutamic peptides were observed in the portal veins of rats administered with WGH. Furthermore, Sato et al (2013) recently demonstrated that pyroglutamyl-leucine (pyroGlu-Leu) is the active component in WGH that exerts hepatoprotective activity. These results suggest that pyroglutamyl peptides, especially pyroGlu-Leu, may be the effective components that act on these inflammatory diseases; however, the underlying mechanism has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in agreement with the results previously reported by Ben Khaled et al (2012) who reported the potential hepatoprotective effect of sardinelle muscle hydrolysates (Sardinella aurita). In the same context, wheat gluten peptides have shown their protective effect against D-galactosamine induced a cute hepatits in rats (Sato et al 2013). …”
Section: Effect Of Fsphs On Hepatic Functionmentioning
confidence: 97%
“…It has recently been revealed that YL also exhibits antidepressant-like activity (Mizushige, unpublished observation). We then investigated whether wheat-derived pyroglutamyl peptides, including pyroGlu-Leu (pEL, Sato et al, 2013) and pyroGlu-Gln-Leu (pEQL), with structural similarity to YL, exhibit antidepressant-like effects in mice.…”
Section: Introductionmentioning
confidence: 99%